PENGARUH KECERDASAN EMOSIONAL, BEBAN KERJA, DAN KUALITAS KEHIDUPAN KERJA TERHADAP TURNOVER INTENTION (Studi Kasus pada PT Ekrut Teknologi Utama) - Putu Angelina Florentina, (2022)
This research is a quantitative study aimed at determining the effect of emotional intelligence, workload, and quality of work life on turnover intention. This study was conducted on 55 PT Ekrut Teknologi Utama employees using saturation sampling method. Path analysis and data processing with SmartPls 3.0 were the analysis techniques used in this study. The following results were obtained from the tests in this study (1) emotional intelligence has a positive and significant effect on turnover intention at PT Ekrut Teknologi Utama, (2) workload has a positive and significant impact on turnover intention at PT Ekrut Teknologi Utama, (3) quality of work life has a negative and significant impact on turnover intention at PT Ekrut Teknologi Utama.